Anomaly Detection and Data Recovery on Mini Batch Distillation Column based Cyber Physical System - Wedar Panji Mardyaningsih; Pranoto Rusmin; Budi Rahardjo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
The development of industrial revolution 4.0 in industrial sector opened a cyber gap for outsiders to pose a threat to the system. Industrial control systems initially designed to meet SRA (Safety, Reliability, and Availability) priorities are now beginning to be pressed to consider security aspects related to the magnitude of the impact that can be caused due to external attacks. In making a safe Cyber Physical System (CPS) based automation, risk assessment will be used to determine the level risk of threat. Mini distillation column batch based CPS will be implemented as the approach of CPS in industrial sector. Anomaly detection based data-driven model and data recovery method is proposed to lower the impact of attack on this system.